Behavior disorders of childhood - Wicks-Nelson, Rita.; Israel, Allen C. (Upper Saddle River, NJ : Prentice Hall, 1997)
A comprehensive, research-based introduction to the field of behaviour disorders of youth. This text includes central issues, with theoretical and methodological studies, descriptions and discussions of many disorders, together with clinical and research information and treatment approaches.
Includes bibliographical references and index.
Keywords: Child psychopathology; Children; Child development